ABO Blood Group and the Risk and Prognosis of Lymphoma - Qin L; Gao D; Wang Q; Zheng X; Wang J; Chen X; Fu D; Ma H; Tan J; Yin Q (Dove Medical Press, 2023)
Ling Qin,1 Dongli Gao,1 Qian Wang,1 Xuewei Zheng,2 Jingjing Wang,2 Xingang Chen,2 Dongliao Fu,2 Haodi Ma,2 Junjia Tan,3 Qinan Yin2 1The First Affiliated Hospital, and College of Clinical Medicine of Henan University of Science and Technology, Luoyang, People's Republic of China; 2Laboratory for Precision Medicine, School of Medical Technology and Engineering, Henan University of Science and Technology, Luoyang, People's Republic of China; 3Section for Statistical Analysis and Data Collection, Luoyang Branch, Bank of China, Luoyang, People's Republic of ChinaCorrespondence: Qinan Yin, School of Medical Technology and Engineering, Henan University of Science and Technology, No. 263 Kaiyuan Avenue, Luoyang, 471000, People's Republic of China, Tel +86-13939928711, Email qinanyin@haust.edu.cnAbstract: ABO blood group antigens exhibit alternative phenotypes and genetically derived structures that are located on the red cell surface. The role of ABO blood group in cancer biology has been intensely reported by several studies, and it is now widely recognized that ABO antigens are associated with the risk and prognosis of several types of tumors, namely gastric cancer and pancreatic cancer. However, there have been contentious limited issues with the association between the ABO blood group and lymphoma. In this narrative review, based on literature data, we discuss the role of ABO blood group in the risk and prognosis of lymphoma and summarize the current knowledge of the underlying pathogenic mechanisms of the association. The possible association of ABO blood group with racial disparities and pathological classification in lymphoma patients is also discussed.Keywords: ABO blood group, lymphoma, survival, disease susceptibility, race